Aspectos demográficos da cobertura de serviços de saneamento no Brasil urbano contemporâneo - Sonaly Cristina Rezende Borges de Lima (2005)
The aim of this study is twofold. First, it intends to characterize the determinants of the existence of public sanitation services in the Brazilian urban households. Second, it intends to analyze the evolution of water supply and sewerage services presence within the country. For achieving these goals two different, but complementary, quantitative analysis are developed. The first one consists of hierarchical models used to identify the mainly determinants of water supply and sewer services presence in the Brazilian urban households. The data set used for performing this exercise comes from the 2000 Brazilian Demographic Census and from the 2000 National Survey of Basic Sanitation. The second one shows the sewer services evolution within the Brazilian urban household through age, period and cohort models (APC). National Household Surveys from 1977, 1982, 1987, 1992, 1997 and 2002 provide the necessary information for this analysis. Both the first and the second studies reveal that variables related with sanitation services supply have a greater impact over the water and sewer services presence than variables related with demand. The hierarchical analysis considered two groups of variables. One comprising the households features influencing services demand and another linked with the countys features affecting water and sewer services supply. The socioeconomic aspects are relevant not only to the household level but also to the county level and both are preponderant to the household sanitation situation. However, variables referring to spatial dimension and management models stand out due to their strong correlation to sanitation public services presence in the urban households. The Southeast households have greater chances of having water and sewer coverage services and, in spite of the states companies hegemonic model, autarchies stand out positively in the sanitation supply services. The APC analysis emphasizes the National Sanitation Plan (PLANASA), from the 70s. The relevant initial investments made by this National Plan were determinants for the water supply and sewerage services coverage expressive expansion within the country. However, the APC analysis unveiled that the services access odds reduced along the time, being the youngest cohorts strongly exposed to the sanitation services exclusion. The household head socioeconomic level was another important aspect for explaining differentials in the sanitation coverage a long the time and among cohorts.